Teacher training and the evaluation dimension - Batini, Federico; Surian, Alessio (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2015)
The paper suggests key issues on the role of the evaluation dimension in relation to educational planning. It addresses such issues by reporting and reflecting on in-service teacher training as implemented in Padova and in Perugia during the academic year 2013- 2014 through the PAS courses. Within such courses evaluation was introduced to teachers as a dimension that supports teachers themselves to monitor their work in progress towards agreed aims and objectives. In this way evaluation becomes mainly a practice to facilitate learning and to improve the learning context. The paper follows up on a previous paper (Batini, Surian, 2011) centred on what was termed as the “Russell paradox”. Such paradox is especially noticeable during teacher training on educational methods. It can be summed up according to the – implicit – recommendation: “Don’t behave as I am behaving with you”.